Marketing Education: Building Capacity beyond Competencies - Vassileva, Bistra (International Journal of Economic Practices and Theories, 2014)
This paper seeks to bring together the notion of marketing leadership and both individual and organisational capabilities by developing marketing leadership framework. The author presents marketing leadership as a way to respond to the changing marketing environment and to the “identity crisis” of marketing science and practice. A combined research and development process is conducted in order to derive a conceptual model of the components of marketing leadership as well as to propose a marketing leadership framework based on both organisational and individual capacity development. This process integrates a broad literature search, both within and outside marketing, followed by a longitudinal study of marketing managers/CEOs to identify the problem areas in marketing leadership and capacity development as well as to find the most important relationship between them. A sequence of qualitative interviews and brainstorming sessions are conducted in order to develop marketing leadership conceptual map. The conceptual map is presented as a framework. Three key capacity areas are identified within the marketing leadership framework namely (1) strategic intent; (2) culture / behaviour; and (3) business processes. The components comprising each of these areas are defined as well as four types of marketing leadership. The author concludes by discussing marketing leadership types and opportunities for further research.